Antenna Control Using EBG - Mohamad Isa, Mohd Sa'ari (2011)
Controllable beam directive antenna has been developed by integrating a TM01 mode patch antenna with an electromagnetic bandgap (EBG) surface. The beam direction is steered when vias in each EBG sector are switched in and out. Each of the six sectors has the vias grouped together for ease of switching. The sector switching steers the radiation beam with a stable antenna reflection coefficient. Radiation patterns are presented showing six sector steering.